AZADIRACHTIN, CARDIOFOLIOSIDE AND KUTKIN CAN BE VITAL PHYTOCHEMICALS FOR THE MODULATION OF SECRETASE ENZYMES FOR THE TREATMENT OF ALZHEIMER’S: AN IN-SILICO ANALYSIS - Anthwal, Prashant (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective:The aim of this study was to screen for active components from medicinal plants of Uttarakhand that has potential for a therapeutic agent for AD by targetingthe secretase enzyme using in-silico approach. Â Methods:Â We used iGEMDOCK for in-silicodocking experiments to screen for active components from medicinal plant, can modulate secretase enzyme. Binding energies for active component from 112 medicinal plants were analyzed. Â Results:Â Our in-silicoanalysis suggests that Cardiofolioside, Azadirachtin, Berberine and Kutkin can best possible candidates for modulation of secretase enzyme and thus hold potential to help patients with AD. The results obtained clearly suggeststhat these active components from plants herbal have the ability to modulate Î± and Î²-secretase either as an activator of Î±-secretase or as an inhibitor of Î²-secretase when compared with known standard drug. Â Conclusion:Â Cardiofolioside, Azadirachtin, Berberine and Kutkin can acts as a modulator for secretase enzymes and these phytochemicals can be exploited for their potential to that of AD.